2002
DOI: 10.1111/j.1349-7006.2002.tb02163.x
|View full text |Cite
|
Sign up to set email alerts
|

Food Restriction Inhibits the Growth of Intestinal Polyps in Multiple Intestinal Neoplasia Mouse

Abstract: The effect of food restriction (FR) on spontaneous intestinal carcinogenesis in multiple intestinal neoplasia (Min) mice was examined. Thirty male Min mice were allotted to ad libitum feeding control and 20% FR groups from six weeks of age until the end of the 13-week experimental period. Although the total number of visible intestinal polyps in the FR group was not significantly different from the control group value, a significant decrease in large-sized polyps ( > > > >2 mm) and an increase in small-sized p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…An increase in physical activity without a change in food intake should have placed the treadmill runners in a state of negative caloric balance. Caloric restriction studies in Apc Min/ϩ mice have demonstrated a decrease on tumor formation and size, which is associated with a decrease in body weight (16,19). The decrease in body weight comes from decreased skeletal muscle and fat.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An increase in physical activity without a change in food intake should have placed the treadmill runners in a state of negative caloric balance. Caloric restriction studies in Apc Min/ϩ mice have demonstrated a decrease on tumor formation and size, which is associated with a decrease in body weight (16,19). The decrease in body weight comes from decreased skeletal muscle and fat.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these studies using Apc Min/ϩ mice point to gender as an important variable in modulating intestinal polyp development. However, a major caveat related to the second study was the extremely low number of intestinal polyps in control Apc Min/ϩ mice compared with other published studies (8,16,33).…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Negative caloric balance induced by restricting caloric intake can prevent the development of tumors in Apc Min/+ mice (15, 20, 21). Likewise, excess consumption of calories can promote tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Studies assessing tumor initiation in the calorie restricted intestine in the same strain of mice and using the same or different (Tsao et al, 2002) genetic cancer models come to divergent conclusions. In general, all of these studies report a reduction in the overall size of adenomas consistent with the anti-growth effects of calorie restriction, but in terms of incidence some report either a neutral or negative effect (Kakuni et al, 2002; Mai et al, 2003). In another study by Weindruch and colleagues, calorie restriction, when started in middle aged mice, actually increased the incidence of spontaneous cancers (Pugh et al, 1999).…”
Section: Diet Stem Cells and Cancer Incidencementioning
confidence: 92%